1981
DOI: 10.2172/6589426
|View full text |Cite
|
Sign up to set email alerts
|

Texas geothermal R D and D program planning support document. Final report

Abstract: or implied, or assume any legal liability or responsibility for t h e accuracy, completeness or usefulness of any information, apparatus, product or process disclosed, or represent that its use would not infringe privately owned rights. The report is a product of t h e efforts of those conducting the project and does not necessarily represent the views of members of TENRAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ginkgo shows tolerance to a suite of gaseous air pollutants, except for a sensitivity to simulated acid rain (Kim, 1987; Oh et al, 1983). It was tolerant to sulphur dioxide, nitrogen oxides and ozone while it was moderately sensitive to fluorides (Davis & Gerhold, 1976; Davis & Wilhour, 1976; Karnosky, 1978; Weinstein, 1977). An investigation on the degree of leaf damage resulting from air pollutants suggested that Ginkgo was more tolerant to air pollution than 15 other trees, namely Pinus koraiensis , Pinus rigida , Abies holophylla , Pinus densiflora , C. japonica , Chamaecyparis pisifera , Chamaecyparis obtusa , Juniperus chinensis , Quercus serrata , Betula platyphylla , Populus occidentalis , Populus euramericana , Prunus jedoensis , Populus alba × glandulos and Paulownia coreana (Oh et al, 1983).…”
Section: Response To Environmentmentioning
confidence: 99%
“…Ginkgo shows tolerance to a suite of gaseous air pollutants, except for a sensitivity to simulated acid rain (Kim, 1987; Oh et al, 1983). It was tolerant to sulphur dioxide, nitrogen oxides and ozone while it was moderately sensitive to fluorides (Davis & Gerhold, 1976; Davis & Wilhour, 1976; Karnosky, 1978; Weinstein, 1977). An investigation on the degree of leaf damage resulting from air pollutants suggested that Ginkgo was more tolerant to air pollution than 15 other trees, namely Pinus koraiensis , Pinus rigida , Abies holophylla , Pinus densiflora , C. japonica , Chamaecyparis pisifera , Chamaecyparis obtusa , Juniperus chinensis , Quercus serrata , Betula platyphylla , Populus occidentalis , Populus euramericana , Prunus jedoensis , Populus alba × glandulos and Paulownia coreana (Oh et al, 1983).…”
Section: Response To Environmentmentioning
confidence: 99%